Anatomical Variations and Therapeutic Approaches of Choledochal Cysts - Muhammad Hilmy As Shiddiq; Imey Pinasty Harianto Putri; Luthfiya Nur Fadhila; Muhammad Fathir Rahadian Ansary; Aulia Putri Mussyafa; I Nyoman Yudayana Indratama; Siti Raodatul Jannah Tunairin; Muhammad Rifki; Arif Zuhan (Indonesian Journal of Health and Medical Education, 2026)
Choledochal cysts are congenital anomalies characterized by abnormal dilatation of the bile ducts, either intrahepatic or extrahepatic. This condition can lead to serious complications, including cholangitis, pancreatitis, and malignancy. Choledochal cysts are more prevalent in Asian populations compared to Western populations and are more commonly observed in females. Timely diagnosis is crucial to prevent further complications. This study aims to conduct a literature review on the anatomical variations and available therapeutic methods for managing choledochal cysts, as well as to evaluate the effectiveness of various treatment approaches. A systematic literature review methodology was employed, involving database identification, keyword selection, article screening, and the use of recent publications from reputable scientific databases such as PubMed, Google Scholar, and Scopus. This review identifies five types of choledochal cysts based on the Todani classification, with Type I being the most common. The primary treatment for choledochal cysts involves complete cyst excision, usually followed by biliary reconstruction using Roux-en-Y hepaticojejunostomy. In more advanced cases, complex surgical procedures such as pancreaticoduodenectomy may be required. Biliary reconstruction following cyst excision, particularly through Roux-en-Y jejunostomy, has been proven effective and is considered the gold standard in choledochal cyst management. Surgical approaches should be tailored to the cyst type to achieve optimal clinical outcomes.